Extended Stochastic Integral and Wick Calculus on Spaces of Regular Generalized Functions Connected with Gamma Measure - Kachanovskii, N.A. (Український математичний журнал, 2005)
We introduce and study an extended stochastic integral, a Wick product, and Wick versions of holomorphic functions on Kondrat'ev-type spaces of regular generalized functions. These spaces are connected with the Gamma measure on a certain generalization of the Schwartz distribution space S′. As examples, we consider stochastic equations with Wick-type nonlinearity. Вводиться та вивчається розширений стохастичний інтеграл, віківське множення та віківські версії голоморфних функцій на просторах (типу Кондратьєва) регулярних узагальнених функцій. Ці простори пов'язані з гамма-мірою на певному узагальненні простору узагальнених функцій Шварца S′. Як приклади розглядаються стохастичні рівняння з нелінійностями віківського типу.